A Study on the Implementation of a Complete Systematic Land Registration Program in Bunut Sub-District, Pelalawan District - Priyo Budi Maryoso; Rendi Prayuda; Meita Istianda (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
This study analyzes the effectiveness of multi-stakeholder collaboration in the implementation of the Complete Systematic Land Registration (PTSL) program in Bunut District, Pelalawan Regency. The PTSL program as a government effort to provide legal certainty over land ownership requires cooperation from various stakeholders in its implementation. With a qualitative approach and case study design, this study uses the collaborative governance framework from Emerson et al. (2012) to analyze three main dimensions of collaboration: principled engagement, shared motivation, and capacity for joint action. Data were collected through in-depth interviews with 27 informants, participant observation, focus group discussions, and documentation studies. The results of the study indicate that multi-stakeholder collaboration in the implementation of PTSL in Bunut District shows varying effectiveness in various dimensions. In the principled engagement dimension, collaboration is quite effective in the aspects of discovery and definition, but is still limited in the aspects of deliberation and determination. In the shared motivation dimension, there are limitations in building mutual trust and understanding between the community and technical agencies. Meanwhile, in the capacity for joint action dimension, there are strengths in the aspects of procedural arrangements and leadership, but significant limitations in the aspects of knowledge and resources. Supporting factors for collaboration include political commitment, community awareness, the role of traditional leaders, effective communication platforms, and academic involvement. Meanwhile, inhibiting factors include differences in interests between stakeholders, limited technical capacity at the village level, communication and coordination problems, historical land complexity, and budget constraints. The study recommends strategies to increase the effectiveness of collaboration through strengthening multi-stakeholder forum institutions, developing technical capacity, increasing transparency and accountability, developing effective conflict resolution mechanisms, strengthening the role of village governments, and allocating adequate resources. The research findings contribute to the development of collaborative governance theory in the Indonesian context, especially in rural areas with unique socio-cultural characteristics.